The Impact of Acquisition on Bentoel Internasional Investama Corporation Financial Performance - Wiwiek Mardawiyah Daryanto; Bramastra Purnomosidhi; Sarah Khairannisa (International Journal of Business Studies, 2019)
Indonesia Tobacco Industry is one of themost prosperous business in the world, globalization made company across the globe racing to acquire tobacco company. Indonesian investment climate allows acquisition conduct by a foreign company in this sector. This study based on the acquisition of PT. Bentoel Internasional Investama (RMBA) by aforeign company (British American Tobacco) in 2010, the data was collected from the annual report of RMBA during 2006- 2015. Four accounting ratio were applied to test the signiicant change in the inancial performance of RMBA five years before and ive years after the acquisition. There is a signiicant difference in the inancial performance of the RMBA between pre and post-acquisition. The signiicant difference can be used as an input to improve RMBA inancial performance. This study provides an empirical analysis before and after acquisition that can be served for a future strategy on acquisition tobacco company in Indonesia.